The clinical value of serum sirtuin-1 in the diagnosis of rheumatoid arthritis: a pilot study. Issue 4 (2nd October 2021) - Li, X; Li, X; Zeng, T; Liu, Y; Hu, T; Huang, J; Wu, Y; Yu, J; Pei, Z; Tan, L
ABSTRACT: Introduction : Cell biology studies, animal models and other data suggest a role for sirtuin-1 in the pathogenesis of rheumatoid arthritis (RA). We hypothesized the clinical significance of serum sirtuin-1 in this disease. Methods : Serum was obtained from 141 RA patients, 144 non-RA patients and 88 healthy controls. Sirtuin-1, anti-mutant citrulline vimentin antibody (anti-MCV), anti-cyclic citrulline polypeptide antibody (anti-CCP), rheumatoid factor and C-reactive protein were measured by immunological methods, and erythrocyte sedimentation rate was determined by the Westergren method. Results : All markers were higher in the RA group than in the non-RA group and the healthy control group (P < 0.01). The specificity of sirtuin-1 for the diagnosis of RA was 97% (the highest among all markers), sensitivity was 71%. In ROC curve analysis, the AUCs (95% CI) of sirtuin-1, anti-CCP and anti-MCV were 0.87 (0.82–0.91), 0.91 (0.88–0.94) and 0.92 (0.89–0.95) respectively (all p < 0.01). The combination of sirtuin-1and anti-MCV gave the highest Youden index of 0.79, whilst Cox regression showed sirtuin-1 and rheumatoid factor were the strongest independent predictors of RA. Conclusions : Serum sirtuin-1 is increased in RA, and may have a place is the diagnosis of this disease when combined with other markers.